Tunica-Specific Transcriptome of Abdominal Aortic Aneurysm and the Effect of Intraluminal Thrombus, Smoking, and Diameter Growth Rate. Issue 11 (November 2020) - Lindquist Liljeqvist, Moritz; Hultgren, Rebecka; Bergman, Otto; Villard, Christina; Kronqvist, Malin; Eriksson, Per; Roy, Joy
Abstract : Objective: There is no medical treatment to prevent abdominal aortic aneurysm (AAA) growth and rupture, both of which are linked to smoking. Our objective was to map the tunica-specific pathophysiology of AAA with consideration of the intraluminal thrombus, age, and sex, and to subsequently identify which mechanisms were linked to smoking and diameter growth rate. Approach and Results: Microarray analyses were performed on 246 samples from 76 AAA patients and 13 controls. In media and adventitia, there were 5889 and 2701 differentially expressed genes, respectively. Gene sets related to adaptive and innate immunity were upregulated in both tunicas. Media-specific gene sets included increased matrix disassembly and angiogenesis, as well as decreased muscle cell development, contraction, and differentiation. Genes implicated in previous genome-wide association studies were dysregulated in media. The intraluminal thrombus had a pro-proteolytic and proinflammatory effect on the underlying media. Active smoking resulted in increased inflammation, oxidative stress, and angiogenesis in all tissues and enriched lipid metabolism in adventitia. Processes enriched with active smoking in control aortas overlapped to a high extent with those differentially expressed between AAAs and controls. The AAA diameter growth rate (n=24) correlated with T- and B-cell expression in media, as well as lipid-related processes in the adventitia. Conclusions: This tunica-specific analysis of gene expression in a large study enabled the detection of features not previously described in AAA disease. Smoking was associated with increased expression of aneurysm-related processes, of which adaptive immunity and lipid metabolism correlated with growth rate. Graphic Abstract: A graphic abstract is available for this article. Abstract : Supplemental Digital Content is available in the text.